(untitled) (Biuletyn Kryminologiczny, 2021)
W prezentowanym artykule podjęto kwestię przestępczości ekologicznej w Polsce na płaszczyźnie historycznej. Uwzględniono w nim aspekty prawne działań wymuszających przestrzeganie norm i prawa ochrony środowiska. Artykuł odnosi się do wymienionych zakresów regulacji legislacyjnych chroniących środowisko w okresie od X w. aż do czasów współczesnych. In this article the issue of environmental crime in Poland will be taken on the level of historical. Legal aspects of activity to standard observance and compliance with environmental requirements will be taken into account. This article will refer to these ranges of environmental legal regulations in the time from X century to the contemporaneity.